A study on customer’s satisfaction toward services provided by Pertubuhan Peladang Kawasan Kuantan Utara (PPKKU) / Muhammad Mahfuz Malek - Malek, Muhammad Mahfuz (Faculty of Business and Management, 2009)
This paper investigates the customer satisfaction level toward products and services offered by PPKKU and also to determine relationship between level of customer satisfaction and factor that might influence it. The investigations are using a questionnaire to gain data. The questionnaire being use is a list of research or survey questions asked to respondents, and designed to extract to specific information to the customers of Pertubuhan Peladang Kawasan Kuantan Utara (PPKKU). Previously, there has been no empirical research on this research about the customers satisfaction in PPKKU. Hence, this research is the first of its kind. A simple regression analysis was conducted to test the relationship between the dependent variables and independent variables. The findings show that all the variables has a positive significant impact on customer satisfaction. In conclusion, these findings suggest that PPKKU should make improvement in their product, price, place, and promotion for the purpose to make customers feel more satisfied and this can give positive impact to PPKKU for example in terms of profit or other positive things in future.